2017
DOI: 10.1016/j.bbmt.2016.12.635
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and the Clinical Impact of Cytomegalovirus and Epstein-Barr Virus Infections in Pediatric Recipients of TCR-α/β– and CD19-Depleted Grafts

Abstract: Alpha/beta T cell and CD19 depletion are used to improve the outcomes of hematopoietic stem cell transplantation (HSCT). We evaluated the burden of cytomegalovirus (CMV) and Epstein-Barr virus (EBV) in pediatric patients after this HSCT type. A cohort of 182 patients with malignant (n = 114) or nonmalignant (n = 68) disorders was transplanted from either matched unrelated (n = 124) or haploidentical (n = 58) donors. The cumulative incidence of CMV and EBV viremia were 51% and 33%, respectively. Acute graft-ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
70
2
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(83 citation statements)
references
References 45 publications
4
70
2
4
Order By: Relevance
“…[7][8][9] Through this approach, it is possible to transfer to the recipient not only donor HSCs but also committed hematopoietic progenitors, as well as mature natural killer (NK) and gd T cells, both these lymphocyte subsets being capable of exerting a protective effect against leukemia cell regrowth and life-threatening infections. 10 Initial clinical results in children with nonmalignant disorders who received haplo-HSCT using this new method of selective T-cell depletion 11 and in small series of pediatric patients with malignancies, some of which were given additional post-transplantation immune suppression, 12,13 were promising, as the reported incidence of GVHD was low, whereas immune reconstitution was improved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7][8][9] Through this approach, it is possible to transfer to the recipient not only donor HSCs but also committed hematopoietic progenitors, as well as mature natural killer (NK) and gd T cells, both these lymphocyte subsets being capable of exerting a protective effect against leukemia cell regrowth and life-threatening infections. 10 Initial clinical results in children with nonmalignant disorders who received haplo-HSCT using this new method of selective T-cell depletion 11 and in small series of pediatric patients with malignancies, some of which were given additional post-transplantation immune suppression, 12,13 were promising, as the reported incidence of GVHD was low, whereas immune reconstitution was improved.…”
Section: Introductionmentioning
confidence: 99%
“…The median time to neutrophil engraftment in the whole study population was 13 days (range, [9][10][11][12][13][14][15][16][17][18][19]; no variable influenced the kinetics of recovery. The median time to platelet engraftment was 11 days (range, [8][9][10][11][12][13][14][15][16][17][18][19][20].…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Next generation sequencing of the γδTCRs revealed that CMV reactivation post allo-HCT induced a clonal proliferation of distinct γδT cell clones, suggesting a γδTCR-mediated response of γδT cells upon CMV infection ●● [92]. Longitudinal analysis of γδT cells in series of allo-HCT recipients demonstrated that γδT cell numbers are significantly higher in recipients with CMV viraemia as compared to recipients without CMV reactivation [9395, 91]. Memory-like γδT cell responses are increasingly recognized, but many questions remain, including the driving ligands and other signal-driving γδT cell responses [96].…”
Section: 3 Potential Strategies To Simultaneously Enhance Nk and γδmentioning
confidence: 99%
“…Известно, что частым осложнением ТГСК, особенно гаплоидентичной, является реактива-ция вирусов группы герпеса: цитомегаловируса (ЦМВ), вируса простого герпеса 6-го типа (ВПГ 6-го типа), вируса Эпштейна-Барр (ВЭБ) [10]. По нашим данным, кумулятивная вероятность ре-активации ЦМВ после ТГСК составила 14,8 %, ВЭБ -22,0 %, ВПГ 6-го типа -44,0 % (рис.…”
Section: реактивация вирусов группы герпеса после транс-плантации гемunclassified